Clarifying the Role of Attachment and Social Compensation on Parasocial Relationships with Television Characters. Issue 2 (14th March 2016) - Rosaen, Sarah F.; Dibble, Jayson L.
Abstract : A cross-sectional survey ( N  = 371) addressed inconsistent findings in previous research regarding the associations between attachment dimensions, social compensation variables (Loneliness, Need to Belong, Social Anxiety), and parasocial relationships. The study disentangled parasocial relationship from parasocial interaction through more careful measurement and investigated parasocial relationships with both liked and disliked television characters. Data revealed associations between parasocial relationships, social compensation variables, and attachment dimensions, but associations differed based on whether the participant referred to a liked or disliked television character. The strength of parasocial relationships with disliked characters was influenced by the interaction of social compensation and attachment dimensions, whereas for liked characters these variables were associated at the main effect level.